Can streetblock 311 physical incivility call count shifts predict later changing on-site conditions? Gauging ecological construct validity of 311 litter calls - Taylor, Ralph B. (Journal of crime and justice, 2024)
Statement of the problem. 311 call data are replacing on-site assessments as a popular alternative metric to gauge urban streetblock conditions, including physical incivilities like litter, trash and rubbish. Work to date, however, has not yet established the ecological construct validity, and thus the meaning, of streetblock 311 call counts for specific physical incivilities. The current work gauges this validity over time. Procedures. Philadelphia open source geolocated 311 data (35,055 streetblocks within all of Philadelphia’s 45 neighborhoods) were combined with streetblock litter scores from two open source on-site assessments made by trained city raters. Following the Hawley/Bursik change framework, this work examined connections between ecological discontinuities in 311 streetblock litter call counts and later ecological discontinuities in on-site litter assessments. Results/implications. Earlier 311 litter call count shifts connected positively albeit modestly to later assessed litter shifts. Nevertheless, so too did earlier call count shifts in a theoretically unrelated category. For this physical incivility, and perhaps others, category-specific streetblock call count shifts have demonstrated some modest convergent predictive validity, but not discriminant predictive validity. This is the first theoretically aligned, streetblock-level ecological change analysis linking 311 calls about a specific physical incivility to a specific corresponding on-site condition. Neighborhood spatiotemporal inequalities surfaced.